Héctor D. Mandrioni, Rilke y la búsqueda del fundamento, Edit. Guadalupe, Buenos Aires, 1971, 435 pp - Corona, Néstor A. (1973)
Fil: Corona, Néstor A. Pontificia Universidad Católica Argentina; Argentina